From Cash to Digital: The Impact of Trust and Cashless Payments on Consumer Behavior - Fatimah, Siska; Novita Lestari, Putri; Putra Samudra, Ferry (Jurnal Manajemen (Edisi Elektronik), 2025)
The rapid progress of information and communication technology has led to the rise of various non-cash payment methods, such as credit cards, digital wallets, and bank transfers, which are increasingly being used. These payment alternatives' ease, speed, and efficiency have significantly influenced consumer behaviour, particularly in urban areas. This study explores the impact of cashless payment adoption and consumer trust on shopping behaviour. The study population consists of residents of Cirebon City aged 20 to 41 years, totalling 134,143 people (BPS Cirebon City, 2024). Based on the Slovin formula, a sample of 399 respondents was chosen using a Simple Random Sampling technique. The collected data was analysed using the SEM-PLS (Partial Least-Structural Equation Modelling) method. The results demonstrate that consumer trust and cashless payment methods significantly impact consumer behaviour. On the other hand, trust is more critical when changing conduct.   Some customers are still hesitant to utilise non-cash transactions because they lack confidence due to a lack of education, have poor knowledge of digital transaction security, and worry about data exploitation. Therefore, increasing consumer awareness and education on secure digital payment systems is crucial to strengthening trust and encouraging the adoption of cashless payments.